Analysis of Opportunities and Threats or Challenges in the International Trade of Handicrafts (A Case Study of Trade Between Indonesia and Japan) - Tithania Anzhani (Journal of Management, Entrepreneurship, and Tourism, 2026)
This study examines the opportunities and threats affecting the international trade of handicrafts between Indonesia and Japan through a qualitative and non empirical conceptual case study approach. The analysis is grounded in the theoretical perspectives of international trade, international marketing, competitive advantage, strategic management, and creative economy. Data were derived from academic literature, government reports, trade statistics, industry publications, and bilateral economic cooperation documents. The findings indicate that the Japanese market offers substantial opportunities driven by demand for authentic cultural products, appreciation of craftsmanship, supportive trade relations, and the expansion of creative economy activities. The analysis also identifies major challenges including intense competition from other exporting countries, strict quality standards, limited export capabilities among small and medium enterprises, weak market intelligence, language barriers, digital capability constraints, and exposure to global economic volatility. The study further demonstrates that sustainable competitiveness requires integrated strategic responses encompassing dynamic capability development, digital transformation, knowledge management, intellectual property protection, entrepreneurship development, and social capital strengthening. The proposed framework contributes to understanding how handicraft industries can achieve long term international competitiveness while preserving cultural value and supporting sustainable economic development.